Vegetable and fruit intake in Australian adolescents: Trends over time and perceptions of consumption - Jongenelis, Michelle; Scully, M.; Morley, B.; Pratt, Steve (Elsevier BV, 2018)
The consumption of vegetables and fruit during adolescence is crucial to ensuring adequate intake of the nutrients required to meet the rapid growth that characterises this developmental period. However, significant reductions in vegetable and fruit intake during adolescence have been observed making the promotion of consumption an important health promotion challenge. To monitor progress in this population segment toward meeting recommended intake levels and identifying at-risk groups, the present study assessed changes in Australian adolescents’ vegetable and fruit consumption over time and identified the demographic factors associated with meeting recommendations. As individuals who are aware of their diet deficiencies are likely to be more receptive to healthy eating interventions, the present study also assessed adolescents’ perceptions of the adequacy of their vegetable and fruit intake and identified the demographic factors associated with correctly perceiving fruit and vegetable intake to be inadequate. Two cross-sectional samples of Western Australian secondary school students aged 12–17 years were surveyed in 2009–2010 (n = 1501) and 2012–2013 (n = 1406). Only 14% of students at Wave 1 and 13% at Wave 2 met the recommended guidelines for vegetable intake while 68% and 71% met the guidelines for fruit intake. Females had significantly greater odds of failing to meet guidelines for vegetable intake than males. Only 50% of students correctly identified their vegetable and fruit intake to be inadequate. The observed very low levels of compliance with vegetable intake recommendations suggest that addressing deficiencies in vegetable consumption should be a primary focus of future nutrition interventions. Efforts should also be made to increase adolescents’ perceptions of the inadequacy of their intake to optimise the effectiveness of schemes designed to improve vegetable and fruit consumption in this population segment.